2022
DOI: 10.1186/s13068-022-02145-7
|View full text |Cite
|
Sign up to set email alerts
|

Engineering proton-coupled hexose uptake in Saccharomyces cerevisiae for improved ethanol yield

Abstract: Background In the yeast Saccharomyces cerevisiae, which is widely applied for industrial bioethanol production, uptake of hexoses is mediated by transporters with a facilitated diffusion mechanism. In anaerobic cultures, a higher ethanol yield can be achieved when transport of hexoses is proton-coupled, because of the lower net ATP yield of sugar dissimilation. In this study, the facilitated diffusion transport system for hexose sugars of S. cerevisiae was replaced by hexose–proton symport. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…However, the ethanol increase achieved in these studies was lower than that observed in the current study. Furthermore, certain approaches have resulted in a trade-off with biomass (de Valk et al, 2022), potentially compromising the maintenance of consistently high ethanol yield in successive batch fermentations, while others have shown limited reusability (Li et al, 2020), incurring potential costs. In this study, His-Fe 3 O 4 , characterized by its biocompatibility and cost-effectiveness, was introduced as an additive for co-culturing with S. cerevisiae .…”
Section: Discussionmentioning
confidence: 99%
“…However, the ethanol increase achieved in these studies was lower than that observed in the current study. Furthermore, certain approaches have resulted in a trade-off with biomass (de Valk et al, 2022), potentially compromising the maintenance of consistently high ethanol yield in successive batch fermentations, while others have shown limited reusability (Li et al, 2020), incurring potential costs. In this study, His-Fe 3 O 4 , characterized by its biocompatibility and cost-effectiveness, was introduced as an additive for co-culturing with S. cerevisiae .…”
Section: Discussionmentioning
confidence: 99%
“…The resulting metabolically engineered strain was then further adapted to anaerobic growth by an evolutionary engineering strategy, based on gradually decreasing oxygen levels from 100% air to 100% N 2 in a sequential batch reactor. The final evolved strains had a 17.2% increased ethanol yield, along with a 44-47.6% decrease in biomass formation [101].…”
Section: Decreasing By-product Formationmentioning
confidence: 99%
“…In the absence of extracellular invertase activity of S. cerevisia, sucrose was internalized by proton symporters using ATP, which led to improving the anaerobic fermentation and ethanol yield from sugar [5]. In addition, the replacement of all endogenous hexose transporters with hexose-proton symport and extracellular invertase (SUC2) can increase ethanol yield and anaerobic growth of S. cerevisiae [41].…”
Section: Sucrose Consumption Of the Wt And Mt Strainsmentioning
confidence: 99%